Pengaruh Harga, Promosi Penjualan, Dan Shopping Lifestyle Terhadap Impulse BuyingPadaPlatform Tiktok Shop - Delvin Ferrary; Lina Lina; Maria Josephine Tyra (LPPM Universitas Multi Data Palembang, 2023)
This research was conducted with the aim of knowing the effect of the variables Price, Sales Promotion,and Shopping Lifestyle on Impulse Buying on the Tiktok Shop Platform. The population in this study are users of theTiktok application with a sample of Tiktok Shop consumers on the Tiktok application. The sample in this study wasdetermined using a non-probability sampling technique with a purposive sampling approach, namely 120 respondents. The results of this study indicate that the variables Price and Shopping Lifestyle partially have a positive andsignificant effect on Impulse Buying on the Tiktok Shop platform. While the Sales Promotion variable partially hasno effect and is not significant on Impulse Buying on the Tiktok Shop platform.